Dialectics of Da'wah, Politics, and Media in Madura (Analysis of RadarMadura.id News Discourse on Gus Miftah Distributing Money in Pamekasan) - Mariyam, Siti; Triyaningsih, Heny (Jurnal Ilmiah Syi'ar, 2024)
This article examines the complex relationship between da'wah and politics in Madura, especially in the context of the politicized phenomenon of da'wah. The main focus is on discourse analysis of the RadarMadura.id news regarding the controversy over Gus Miftah distributing money in Pamekasan: how the media constructs the story through word choice and grammar to build a narrative related to this issue. This research is a qualitative study that uses discourse analysis as part of the interpretive method. The object of this research is news on RadarMadura.id with the title "Bawaslu Pamekasan Akan Panggil Gus Miftah terkait Aksi Bagi-Bagi Uang" published on January 5, 2024. The news was analysed using the discourse analysis model of Roger Fowler et al which focuses on the analysis of word elements and grammar. The research results show that news reports depict this action as part of the alms routine. The media limits its views by focusing on responding to viral videos and relying on secondary sources to confirm information, rather than conducting in-depth investigations. There is also a discourse battle between the public who supports the idea of money politics and the media which highlights clarification and alms routines. Linguistically, RadarMadura.id uses active sentences to describe events, however, the use of nominalization may influence the interpretation of the actors involved. That is, this analysis shows how the media uses language to build narratives and influence public perceptions, even though they tend to be neutral in their presentation of controversial issues.